Integrating a Multidisciplinary Pain Team and Chiropractic Care in a Community Health Center: An Observational Study of Managing Chronic Spinal Pain - Christopher Prater; Melissa Tepe; Patrick Battaglia (SAGE Publishing, 2020)
Background Chronic spinal pain is one of the most common diseases in the United States. Underserved patients are most affected, and disproportionately may use opioid medications as they lack access to other therapies. It is therefore important to develop systems to treat spinal pain within the primary medical home. Methods We designed a prospective observational pilot study at a community health center to measure the effectiveness of two interventions among an underserved population: a multidisciplinary pain team and chiropractic care. Study outcomes were pain and functional disability measured by the Pain Disability Questionnaire (PDQ), and reduction of opioid dose at baseline and 6-12 months. Multivariate linear regression was used to determine associating factors for change in PDQ scores. Results Thirty-five individuals completed baseline and follow-up PDQs from August 2018 to May 2020. Overall, the mean baseline PDQ was 92.4 +/− 6.1 and the mean follow-up PDQ was 81.9 +/− 7.7, resulting in a mean improvement of −10.6 (95% CI 1.2 - −22.3, P  = .08). Participants in the chiropractic team (mean change −25.0, P  = .01) and those completing the study before COVID-19 (mean change = −22.6, P  < .01) were found to have significantly greater improvement at follow-up. Conclusion This observational study within a community health center resulted in improvement in spinal pain and disability with chiropractic care versus a multidisciplinary pain team. Offering similar services in primary care may help to address pain and disability, and hopefully limit external referrals, advanced imaging, and opioid prescriptions.